2021
DOI: 10.3389/fpsyt.2021.634332
|View full text |Cite
|
Sign up to set email alerts
|

Personality Functioning and Mentalizing in Patients With Subthreshold or Diagnosed Borderline Personality Disorder: Implications for ICD-11

Abstract: The 11th revision of the International Classification of Diseases for Mortality and Morbidity Statistics (ICD-11) defines personality disorder according to personality functioning, which relates to self- and interpersonal functioning. The aim of the present study was to assess the relationship between mentalizing and personality functioning in patients with subthreshold or diagnosed borderline personality disorder. A total of 116 eligible participants were included. Mentalizing was assessed using the Mentaliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 76 publications
(103 reference statements)
1
3
0
Order By: Relevance
“…Thus, higher levels of general personality pathology are accompanied by more difficulties in mentalizing emotions of others. This finding complements existing evidence on associations between mentalizing and personality functioning [13][14][15]. The results are all the more compelling because they show that impairments in cognitive empathy are linked not only to general personality pathology in the form of personality functioning, which conceptually has a strong link to cognitive empathy, but also to general personality pathology based on the models of pathological personality traits and DSM-5 Section II PDs, both of which conceptually only contain scattered references to deficits in cognitive empathy.…”
Section: Cognitive and Emotional Empathy As Markers Of General Person...supporting
confidence: 86%
See 1 more Smart Citation
“…Thus, higher levels of general personality pathology are accompanied by more difficulties in mentalizing emotions of others. This finding complements existing evidence on associations between mentalizing and personality functioning [13][14][15]. The results are all the more compelling because they show that impairments in cognitive empathy are linked not only to general personality pathology in the form of personality functioning, which conceptually has a strong link to cognitive empathy, but also to general personality pathology based on the models of pathological personality traits and DSM-5 Section II PDs, both of which conceptually only contain scattered references to deficits in cognitive empathy.…”
Section: Cognitive and Emotional Empathy As Markers Of General Person...supporting
confidence: 86%
“…Accordingly, a study found that clinician-assessed mentalizing and personality functioning were highly correlated with each other, while empathy was the domain with the highest association with mentalization [13]. Associations between mentalization and personality functioning could also be found when using self-reports [14, 15]. Furthermore, a study found that impairments in personality functioning, assessed with the Operationalized Psychodynamic Diagnosis System [16], were highly associated with deficits in self-reported trait emotional intelligence [17], which entails aspects of emotional empathy.…”
Section: Introductionmentioning
confidence: 99%
“…Another construct related to personality functioning is mentalization, the capacity to elaborate on other people's state of mind and intentions (Bateman and Fonagy, 2004;Luyten et al, 2020). Mentalization was found to overlap conceptually and operationally with Criterion A (Bender et al, 2011;Zettl et al, 2020;Rishede et al, 2021). Furthermore, fostering social cognition competences by improving mentalization capacities is a common element in all therapies of borderline personality disorder (BPD; Bateman and Fonagy, 2004;Viviani et al, 2011;Fischer-Kern et al, 2015;Buchheim and Diamond, 2018;Fonagy et al, 2019;Labek et al, 2019;Lüdemann et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Assuming personality pathology, mentalizing capacity and personality functioning as related concepts, a significant relationship between severity of borderline symptomatology and interpersonal functioning mediated by mentalizing capacity was found [ 86 ]. Early intervention in patients with low treatment expectancy might focus on mentalization capacity to improve interpersonal functioning, which could increase treatment expectancy.…”
Section: Discussionmentioning
confidence: 99%